2021
DOI: 10.1002/advs.202103023
|View full text |Cite
|
Sign up to set email alerts
|

Position‐Scanning Peptide Libraries as Particle Immunogens for Improving CD8+ T‐Cell Responses

Abstract: Short peptides reflecting major histocompatibility complex (MHC) class I (MHC‐I) epitopes frequently lack sufficient immunogenicity to induce robust antigen (Ag)‐specific CD8+ T cell responses. In the current work, it is demonstrated that position‐scanning peptide libraries themselves can serve as improved immunogens, inducing Ag‐specific CD8+ T cells with greater frequency and function than the wild‐type epitope. The approach involves displaying the entire position‐scanning library onto immunogenic nanoliposo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 84 publications
0
7
0
Order By: Relevance
“…In this dataset, most tumor-reactive cells recognized gp70 423–431 , given the segregation of tetramer-binding clusters (clusters 0, 2, 5, 6, 8, 9, 12) from Tet-negative clusters (clusters 1, 3, 4, 7, 10, 11, 13), and the limited presence of Tet-negative cells within these tetramer-binding clusters. However, a few CD8 + TILs did not recognize the tetramer but were within specific tetramer-positive clusters (clusters 2 and 6), suggesting they may recognize another antigen within the TME ( 44 ). The antigen-specific clusters had a mix of Tet-High and Tet-Low cells, both by cell counts ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this dataset, most tumor-reactive cells recognized gp70 423–431 , given the segregation of tetramer-binding clusters (clusters 0, 2, 5, 6, 8, 9, 12) from Tet-negative clusters (clusters 1, 3, 4, 7, 10, 11, 13), and the limited presence of Tet-negative cells within these tetramer-binding clusters. However, a few CD8 + TILs did not recognize the tetramer but were within specific tetramer-positive clusters (clusters 2 and 6), suggesting they may recognize another antigen within the TME ( 44 ). The antigen-specific clusters had a mix of Tet-High and Tet-Low cells, both by cell counts ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…TCR engagement is the most significant contributor to the transcriptional profile of TILs as was established by the differences between tetramer-negative and -positive cells, which divided the UMAP space. A sub-dominant TAA from the CT26 tumor, gp70 37–44 , has been identified from the same endogenous retrovirus as gp70 423–431 ( 44 ), and CT26 cells have numerous point mutations in expressed genes ( 46 ). Thus, there is a possibility for T-cell recognition of these peptides, explaining the presence of some tetramer-negative cells within predominantly tetramer-positive clusters.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, CoPoP was incorporated into a 25 nm covalently circularized nanodisc to examine whether a mosaic nanodisc decorated with spike proteins from different variants can direct the immune system to produce broadly neutralizing antibodies thanks to dilution of immune dominant, variant specific epitopes with little to no effect on the conserved epitopes and thus favoring immune-recessive conserved epitopes [33]. The plug-and-display approach enabled by CoPoP technology allowed a straightforward production of mosaic nanodisc with different spikes attached randomly [26,34]. We previously reported that 1:4000 cNW50: lipid ratio was used to form a 50 nm nanodisc when 3:2 POPC: POPG lipids were used [31].…”
Section: Resultsmentioning
confidence: 99%
“…no effect on the conserved epitopes and thus favoring immune-recessive conserved epitopes [33]. The plug-and-display approach enabled by CoPoP technology allowed a straightforward production of mosaic nanodisc with different spikes attached randomly [26,34]. We previously reported that 1:4000 cNW50: lipid ratio was used to form a 50 nm nanodisc when 3:2 POPC: POPG lipids were used [31].…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, it is di cult to capture tumor-speci c CD8 + T cells using the widely used method of cellular indexing of transcriptomes and epitopes or T cell receptor sequencing 6 . As an alternative, murine tumor models of well-recognized tumor-associated antigens can be used for accurate tumor-speci c CD8 + T cell detection 7,8 . Murine studies and clinical data have indicated that increased frequencies of tumor-localized and peripheral tumor-speci c CD8 + T cells correlate highly with improved TNBC survival 9,10 .…”
Section: Introductionmentioning
confidence: 99%